Mesenchymal stem‐cell potential in cartilage repair: an update. Issue 12 (29th October 2014) - Mazor, M.; Lespessailles, E.; Coursier, R.; Daniellou, R.; Best, T. M.; Toumi, H.
Abstract Articular cartilage damage and subsequent degeneration are a frequent occurrence in synovial joints. Treatment of these lesions is a challenge because this tissue is incapable of quality repair and/or regeneration to its native state. Non‐operative treatments endeavour to control symptoms and include anti‐inflammatory medications, viscosupplementation, bracing, orthotics and activity modification. Classical surgical techniques for articular cartilage lesions are frequently insufficient in restoring normal anatomy and function and in many cases, it has not been possible to achieve the desired results. Consequently, researchers and clinicians are focusing on alternative methods for cartilage preservation and repair. Recently, cell‐based therapy has become a key focus of tissue engineering research to achieve functional replacement of articular cartilage. The present manuscript is a brief review of stem cells and their potential in the treatment of early OA (i.e. articular cartilage pathology) and recent progress in the field.